2022
DOI: 10.3390/toxins14100661
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Blue Native/SDS Polyacrylamide Gel Electrophoresis for Analysis of Brazilian Bothrops Snake Venoms

Abstract: Viperidae snakes are the most important agents of snakebites in Brazil. The protein composition of snake venoms has been frequently analyzed by means of electrophoretic techniques, but the interaction of proteins in venoms has barely been addressed. An electrophoretic technique that has gained prominence to study this type of interaction is blue native polyacrylamide gel electrophoresis (BN-PAGE), which allows for the high-resolution separation of proteins in their native form. These protein complexes can be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…After trying a series of decellularization protocols, we eventually developed a PLA2 decellularized method for conjunctival tissue regeneration. PLA2 is the low molecular mass enzymes (13-16 kDa) that specially hydrolyze phospholipid [16], and exhibit no enzymatic reaction site on the collagen that ECM were well preserved (figure 4). There was a significant decrease in the DNA of renal cells treated with decellularization, and the CCK-8 results indicated that the decellularized tissues did not reduce chondrocyte proliferation compared to the control group (figures 6(A) and (B)).…”
Section: Discussionmentioning
confidence: 99%
“…After trying a series of decellularization protocols, we eventually developed a PLA2 decellularized method for conjunctival tissue regeneration. PLA2 is the low molecular mass enzymes (13-16 kDa) that specially hydrolyze phospholipid [16], and exhibit no enzymatic reaction site on the collagen that ECM were well preserved (figure 4). There was a significant decrease in the DNA of renal cells treated with decellularization, and the CCK-8 results indicated that the decellularized tissues did not reduce chondrocyte proliferation compared to the control group (figures 6(A) and (B)).…”
Section: Discussionmentioning
confidence: 99%
“…The species of B. jararaca and B. neuwiedi reach around 120 and 60 cm in length, respectively, while B. jararacussu is the largest (160–220 cm). In general, the venoms of Bothrops are a mixture of protein/peptide families, such as the snake venom metalloproteases (SVMPs), snake venom serine proteinases (SVSPs), phospholipase A 2 (PLA 2 ) enzymes, L-amino acid oxidases (LAAOs), hyaluronidases, and bradykinin potentiators, which are responsible for the venom toxicity [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%